The LINK-A lncRNA interacts with PtdIns(3,4,5)P3 to hyperactivate AKT and confer resistance to AKT inhibitors - Lin, A.; Hu, Q.; Li, C.; Xing, Z.; Ma, G.; Wang, C.; Li, J.; Li, J.; Yao, J.; Liang, S.; Wang, S.; Park, P. K.; et al.
Phosphatidylinositol-3,4,5-trisphosphate (PtdIns(3,4,5)P3 or PIP3)mediates signalling pathways as a second messenger in response to extracellular signals. Although primordial functions of phospholipids and RNAs have been hypothesized in the 'RNA world', physiological RNA-phospholipid interactions and their involvement in essential cellular processes have remained a mystery. We explicate the contribution of lipid-binding long non-coding RNAs (lncRNAs)in cancer cells. Among them, long intergenic non-coding RNA for kinase activation (LINK-A)directly interacts with the AKT pleckstrin homology domain and PIP3 at the single-nucleotide level, facilitating AKT-PIP3 interaction and consequent enzymatic activation. LINK-A-dependent AKT hyperactivation leads to tumorigenesis and resistance to AKT inhibitors. Genomic deletions of the LINK-A PIP3-binding motif dramatically sensitized breast cancer cells to AKT inhibitors. Furthermore, meta-analysis showed the correlation between LINK-A expression and incidence of a single nucleotide polymorphism (rs12095274: A > G), AKT phosphorylation status, and poor outcomes for breast and lung cancer patients. PIP3-binding lncRNA modulates AKT activation with broad clinical implications.